Krukenberg Tumor in A 22 Year Old Patient with Primary Tumor in the Transverse Colon. Clinical Case - Arredondo, Guillermo Padron (Archives of Clinical and Medical Case Reports, 2017)
Background: In 1896 Friedrik Krukenberg described a bilateral ovarian tumor, which he called "mucocellular ovarii fibrosarcoma" (carcinomatodes), considering it to be fibrosarcomatous in nature. Clinical Case: A 22-year-old female patient admitted to the emergency department of our hospital with grade IV anemic syndrome. Two weeks after his admission to the emergency room, he presented melenic evacuations accompanied by asthenia, adynamia, hyporexia and dyspnea. His vital signs were normal except for TA 100/60 mmHg. Their laboratories of admission showed a hemoglobin of 6.3 g rest within normal parameters; Guayaco (++). First Ultrasound reported thickening of the colon walls. His control blood biometry reported hemoglobin of 3.4 g being transfused with globular packages increasing to 12.8 g. Carcinoembryonic antigens reported CA 19.9, 315.27, 15.3 = 7.29. A panendoscopy and colonoscopy was performed, reporting ulcerated lesions in the transverse stenotic colon. It refers to a Regional Hospital of High Specialty to the service of oncology for its integral management. Discussion: Previously, any metastatic ovarian cancer was categorized as Krukenberg's tumor; however, Novak and Gray established new diagnostic criteria to eliminate this confusion. Therefore, a mucin-secreting carcinoma with ring-seal cells in an ovarian fibroblast stroma is a Krukenberg tumor. Most of these tumors are of gastric origin (76%). Colorectal cancers carry a poor 5-year survival prognosis of only 13.1%.